Principles of laparoscopic surgery : basic and advanced techniques - Arregui, Maurice E; Way, Lawrence W (Springer, 1995)
This book brings together the most up-to-date information available on basic and advanced laparoscopic techniques. Enhanced by over 750 illustrations and written by international, interdisciplinary experts, this is the definitive reference on: basic laparoscopy techniques; laparoscopy and thoracoscopy in general surgery; laparoscopy in surgical subspecialties (gynecology, urology, angioscopy); plus a special section on technological aspects of laparoscopy. Throughout this authoritative volume, the reader will find in-depth reviews of the literature and extensive clinical and scientific data on the rationale for using laparoscopic surgical procedures.
Keywords: laparoskopie; Laparoscopy; chirurgie; radiologie, nukleární medicína a zobrazovací metody